A face gear grinding method and its experimental verification using cylindrical internal gear grinding machine - ZHANG Congcong; CAO Xuemei; DENG Xiaozhong; HAN Zhengyang; AN Xiaotao; XU Hao (Xibei Gongye Daxue Xuebao)
According to the structure of a machine tool, the mathematical model of face gear grinding with a disc grinding wheel is established. The face gear tooth surface equation that contains the machine tool parameter errors is derived, and the influence of the parameter errors on the topological deviation of the tooth surface is analyzed. The experiments on face gear grinding are completed with the cylindrical internal gear grinding machine and detected in the gleason gear detection center. The maximum tooth surface deviation is -24.6 μm, verifying the feasibility of the proposed grinding method and the correctness of the machine tool parameter adjustment method. The use of the general cylindrical internal gear grinding machine to grind face gears without special face gear machine tool is of great significance for the promotion of face gears and the reduction of manufacturing cost.